Respon Pemberian Dosis Pupuk Organik Cair Terhadap Pertumbuhan Bibit Tanaman Kakao (Theobroma cacao L.) - Rukmia; Fandi Ahmad; Adnan, Adnan; Ramadhan, Aditya (Permaculture: Jurnal Ilmu Pertanian & Lingkungan, 2025)
This study aims to determine the response of liquid organic fertilizer with different doses to the growth of cocoa seedlings. This study was conducted in Kalangkangan Village, Galang District, Tolitoli Regency, Central Sulawesi Province. The study was conducted from April to July 2018. This study used a Completely Randomized Design (CRD) consisting of 6 treatment levels, namely: No treatment (P0), liquid organic fertilizer dose of 1 ml / liter of water (P1), liquid organic fertilizer dose of 2 ml / liter of water (P2), liquid organic fertilizer dose of 3 ml / liter of water (P3), liquid organic fertilizer dose of 4 ml / liter of water (P4), and liquid organic fertilizer dose of 5 ml / liter of water (P5). Each treatment was repeated 3 times so that there were 18 research units. The results showed that the treatment of liquid organic fertilizer dose of 2 ml / liter of water gave better results on the growth of cocoa seedlings, both in the root length parameter, which was 51.53 cm. Likewise, in the root volume observation parameters, the provision of liquid organic fertilizer with a dose of 2 ml/liter of water also gave better results, namely an average of 11.00 ml, compared to other liquid organic fertilizer dose treatments.